Prevalence, knowledge and attitudes toward herbal medication use by Saudi women in the central region during pregnancy, during labor and after delivery - Sameer Al-Ghamdi; Khaled Aldossari; Jamaan Al-Zahrani; Fawaz Al-Shaalan; Saad Al-Sharif; Hamad Al-Khurayji; Aiman Al-Swayeh (BMC, 2017)
Abstract Background Herbal medication usage is prevalent in both developing and developed countries. The low level of awareness of the possible dangers of some herbs during pregnancy increases the risk of unwarranted sequelae. This manuscript describes the first study of herbal medication use among pregnant women in Saudi Arabia. It aims to determine the prevalence of herbal medication use during pregnancy, during labor and after delivery in the central region of Saudi Arabia. Methods A cross-sectional descriptive study was conducted over a 5-month period from May 15 to October 15, 2016. A self-administered questionnaire was distributed at 4 main hospitals and 3 primary care centers in Riyadh and Al Kharj. Data from 612 participants were collected and analyzed. Descriptive statistics in the form of frequency and percentage were determined, and Chi-squared tests were performed. Results Of the 612 participants, 25.3%, 33.7% and 48.9% used herbs during pregnancy, during labor, and after delivery, respectively. The primary motives for using herbal medication during pregnancy, during labor and after delivery were to boost general health, ease and accelerate labor and clean the womb, respectively. There was a significant association between use during pregnancy and prior use (P = 0.001). Most pregnant women used herbs based on advice from family and friends (52.9%). Only 40.7% of pregnant women disclosed their herbal use to their doctors. Conclusion The prevalence of herbal medication use among pregnant Saudi women in Riyadh and Al Kharj is relatively high. Doctors should be aware of evidence regarding the potential benefits or harm of herbal medication use during pregnancy.